Plants used for bone fracture by Indigenous folklore of Nizamabad district, Andhra Pradesh - Dinesh, Vijigiri; Sharma, P P (International Multidisciplinary Research Journal, 2013)
The present investigation provides information on the therapeutic properties of 17 crude drugs used for treating bone fracture by the natives of Nizamabad District. Of these, 12 species are not reported earlier for the bone fracture in major literature published so far. Information on botanical name, vernacular name, family, part used, mode of medicine preparation and administration is provided.